ANALISA GAMBARAN PENGELOLAAN RETUR OBAT DI RAWAT INAP RUMAH SAKIT dr. ABDUL RADJAK SALEMBA JAKARTA - Pricillya Maria Loimalitna; Putri Ekasari; Sigit Pamungkas (Jurnal Farmasi IKIFA, 2024)
The purpose of this research is to find out the drug return management system and the percentage of reasons for returns that most often occur, as well as the percentage of total drug return items at Dr. Abdul Radjak Salemba in January–March 2023. This research is non-experimental and descriptive in nature. Data was collected prospectively, namely by observing and evaluating return sheets taken from a sample of inpatient returns during January–March 2023. The population is all prescription transactions for inpatient patients at Dr. Abdul Radjak Salemba for the period January–March 2023. Sampling in this study used the total sampling technique. After the research was carried out, there were five reasons for returns: stopping therapy, duplicating prescriptions, extra therapy, returning patients, and passing away. Obtaining the highest percentage of duplication of prescriptions with a percentage of 42.27%, patients returning 39.01%, extra therapy 13.52%, stopping therapy 5.07%, and death 0.13%. As well as the percentage of total item returns of 19.62% in January, 17.11% in February, and 18.03% in March, Dr. Hospital Abdul Radjak Salemba had to design a drug distribution system from (one daily dose dispensing) ODD to (unit dose dispensing) UDD in order to reduce the rate of drug returns at Dr. Abdul Radjak Salemba. With or without reducing the quality of pharmaceutical services.